IMPLEMENTASI SISTEM INFORMASI PERAMALAN STOK JENIS KOMODITI TANAMAN PANGAN DI ACEH UTARA - Angga Pratama; Salamah Salamah (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2018)
Commodity types of food crops are one of the sectors that are very important for food security, and this is very influential in maintaining food security in Indonesia. Food crops commodities in northern Aceh that have commodities include rice, soybeans, corn, peanuts, green beans and so on. The problem now is the difficulty of finding information which is an obstacle to analyzing the stock model of the types of food crops. This commodity plays an important role in people's lives in the next few years. There is a forecasting information system to be able to see all the information on the stock inventory report of food crop commodities in the future. The Double Exponential Smoothing model is very appropriate because the behavior of the commodity type data is seasonal (per month) and trend (increase). With annual data reaching 47716.14 tons for rice plants, for soybeans reached 6141.81 tons. Estimated forecast for January-December. On average every January 32600, February 32300, March, 31200, April 29500, May 38000, November 29500, December 35800 for the following year experienced an increase. Next to the value of Set Alpha 0.2. The period of one for the value of'tt is 32600, the value of s''t is 32600 for at is 32600, for the value of bt is 0, then in the second period of value, the'tt is 32540, the value of s''t is 32588 for at is 32492, for the value of bt is -12. Furthermore for the period 25, Shout is 35360, the value of no is 33228.94109 for at 37491.05891, for the value of bt is 532.7647285, and for the period 26 the last is Shutter is 33340, the value is 33251.15287 for at is 33428.84713, for the value of bt is 22,21178279. The next prediction result of rice commodity 33451.05 and mape error value is 0.334216418% with alpha set value 0.2.Keywords: Information System, DES, Type of Food Crop Commodity